Analysis of the Influence of Legal, Social, and Political Factors on Religious Freedom in Indonesia - Harsya, Rabith Madah Khulaili; Mokodenseho, Sabil; Silaban, Yabes Sentosa; Zuwanda, Zulkham Sadat (West Science Law and Human Rights, 2024)
This research investigates the influence of legal, political, and social factors on religious freedom in Indonesia through a quantitative analysis. A sample of 150 participants was surveyed, and a structural equation model was employed to examine the relationships between these factors and their impact on perceptions of religious freedom. The results reveal significant positive associations between legal awareness, political dynamics, social attitudes, and religious freedom. The study contributes valuable insights for policymakers, legal practitioners, and advocacy groups seeking to enhance religious freedom in Indonesia